Characterization of the Interleukin-28B Gene rs12979860 C/T Polymorphism in Turkish Chronic Hepatitis C Patients and Healthy Individuals - Serpil Taheri; Halit Canatan; Bilgehan Aygen; Orhan Yıldız; Keziban Korkmaz; Gökmen Zararsız (Balkan Medical Journal, 2015)
Background: Host genetic factors can affect the progress of hepatitis-C virus (HCV) infection. Interleukin-28B (IL28B) single nucleotide polymorphisms may play an important role in the clearance of HCV spontaneously or with treatment.